Significantly improved solvent tolerance of Escherichia coli by global transcription machinery engineering. Issue 1 (December 2015) - Zhang, Fa; Qian, Xiaohong; Si, Haiming; Xu, Guochao; Han, Ruizhi; Ni, Ye
Abstract Background Escherichia coli has emerged as a promising platform microorganism to produce biofuels and fine chemicals of industrial interests. Certain obstacles however remain to be overcome, among which organic-solvent tolerance is a crucial one. Results We used global transcription machinery engineering (gTME) to improve the organic-solvent tolerance (OST) ofE. coli JM109. A mutant library of σ70 encoded byrpoD was screened under cyclohexane pressure.E. coli JM109 strain harboring σ70 mutant C9 was identified with capability of tolerating 69 % cyclohexane. TherpoD mutant contains three amino-acid substitutes and a stop-codon mutation, resulting a truncated sequence containing regions σ1.1 and σ1.2 . Total protein difference produced byE. coli JM109 strain harboring C9 was examined with 2D-PAGE, and 204 high-abundant proteins showed over twofold variation under different solvent stress. Conclusions Our results show that several genes (gapA, sdhB, pepB anddppA ) play critical roles in enhanced solvent tolerance ofE. coli, mainly involving in maintaining higher intracellular energy level under solvent stress. Global transcription machinery engineering is therefore a feasible and efficient approach for engineering strain with enhanced OST-phenotype.